Meningkatkan Literasi Sejarah Lokal Peserta Didik SMK Negeri 2 Wonogiri Melalui Bahan Ajar Digital Perjuangan Mangkunegara I - Wiganingrum, Anditya (Jurnal Ilmiah Global Education, 2025)
Literacy is one of the skills that must be possessed by students in industry 4.0 and is an important part of implementing the Merdeka Curriculum. Improving literacy skills can be integrated into history learning. Local history literacy is the skill of students to understand local history in their surrounding areas contextually. The low interest and ability of local history literacy students in Vocational High Schools towards history learning is one of the interesting problems to study. This study aims to examine the implementation of digital teaching materials on the struggle of one of the heroes, namely Mangkuengara I, to improve the local history literacy of students at State Vocational High School 2 Wonogiri. Digital teaching materials are expected to be an alternative medium for students for effective and innovative history learning in line with current technological developments. This study uses a qualitative method with a case study approach. The data collection techniques used are observation, interviews, and documentation. The results of the study indicate that the use of digital teaching materials in the struggle of Mangkunegara I can improve the interest and ability of local history literacy of students at State Vocational High School 2 Wonogiri.